Synthesis and Evaluation of 11-Butyl Matrine Derivatives as Potential Anti-Virus Agents - Wanjun Ni; Lizhong Wang; Hongjian Song; Yuxiu Liu; Qingmin Wang (Molecules, 2022)
Matrine derivatives were reported to have various biological activities, especially the ester, amide or sulfonamide derivatives of matrine deriving from the hydroxyl or carboxyl group at the end of the branch chain after the D ring of matrine is opened. In this work, to investigate whether moving away all functional groups from the C-11 branch chain could have an impact on the bioactivities, such as anti-tobacco mosaic virus (TMV), insecticidal and fungicidal activities, a variety of N-substituted-11-butyl matrine derivatives were synthesized. The obtained bioassay result showed that most N-substituted-11-butyl matrine derivatives had obviously enhanced anti-TMV activity compared with matrine, especially many compounds had good inhibitory activity close to that of commercialized virucide Ningnanmycin (inhibition rate 55.4, 57.8 ± 1.4, 55.3 ± 0.5 and 60.3 ± 1.2% at 500 μg/mL; 26.1, 29.7 ± 0.2, 24.2 ± 1.0 and 27.0 ± 0.3% at 100 μg/mL, for the in vitro activity, in vivo inactivation, curative and protection activities, respectively). Notably, N-benzoyl (7), N-benzyl (16), and N-cyclohexylmethyl-11-butyl (19) matrine derivatives had higher anti-TMV activity than Ningnanmycin at both 500 and 100 μg/mL for the four test modes, showing high potential as anti-TMV agent. Furthermore, some compounds also showed good fungicidal activity or insecticidal activity.